SPORT IN THE SCHOOL CONTEXT: PUBLICATIONS IN BRAZILIAN JOURNALS BETWEEN 1990-2019 - Silva Junior, Edesio Rodrigues da (2022)
The study aims to present an overview of studies produced on sport in the school context, focusing on the production of scientific articles exposed in national journals in the area of Physical Education and Sports. We used eleven journals as a source of this investigation, in the time frame of 1990-2019. The articles were classified into: (a) sport in school physical education classes, (b) sport in extracurricular programs at school. The data reveal a growing interest in sport in the school context over the years. It was identified that most of the articles were published in the last decade investigated and the highest incidence of articles is related to sport in school physical education classes. Therefore, the school assumes an important role as a context for the access and path of young people in sport.